Kearifan Lokal dan Strategi Pengelolaan Potensi Tumbuhan Api-api (Avicennia Sp.) dalam Restorasi Ekosistem Mangrove - Anang Kadarsah; Nurul Huda (Journal of Tropical Ethnobiology, 2021)
Combination services by Avicennia sp. as a pioneering plants with local wisdom is the best asset in carrying out the program of mangrove ecosystem restoration. The purpose was to describe the knowledge, attitudes and participation of residents in developing the potential of Avicennia sp. for mangrove ecosystem restoration in Pagatan Besar Village, Tanah Laut, South Kalimantan. Literature review and in-depth interviews are used to obtain local wisdom data and formulate management strategies. The results indicated that knowledge of Avicennia sp. is very high (94%) and as a medicinal plant (97%). However, most (93%) do not know if it can be used as food or for mangrove ecosystem restoration (94%). They also agrees with the prohibition of logging (90%) but disagrees (96%) with taking part of it. Regarding the appeal, 94% of them is needed to plant and 88% needed regulations to keep mangrove forests clean. Regarding the activities (from 100% Banjarese with male and female ratio of 63: 47%), seedling maintenance is the highest priority for restoration. Meanwhile, dumping waste is the most disturbing activity. Based on active ingredients, it can be used as raw materials for medicine, wound healing, antioxidants, antimicrobials, antifungials, and anti-inflammatory. Also, its potentials as food ingredients, fish and noodle bioformalin. It has the best growth for restoration at salinity 22.5-30 ppt and spacing of 75 cm. The type III strategy can be applied for Avicennia Sp. management in Pagatan Besar Village through restoration training, empowering plant potential, implementing regulations, and determining land status.